Analisis Tanggung Jawab Etika Profesi Pengacara Dan Hakim Dalam Mewujudkan Keadilan - Dito Aditia Darma Nst; Grace Jasmine Sinaga; Haka Haka; Khanif Amar Lubis; Nany Erasti Sianturi; Nathanael Marvelino Saragih Sidauruk; Frendy Sihotang (Journal of Innovative and Creativity, 2025)
Professional ethics, lawyers, judges, justice, and professional responsibility are crucial elements in the judicial system to ensure fair and credible legal decisions. This study analyzes the ethical responsibilities of lawyers and judges and their impact on substantive justice using a descriptive qualitative approach based on literature review and legaldocument analysis. The literature indicates that lawyers who uphold professional ethics maintain transparency, professionalism, and protect client rights, while judges who adhere to integrity, independence, and objectivity can render fair and trusted decisions. The study also identifies challenges in implementing professional ethics, including conflicts of interest, external pressures, and uneven understanding of ethical principles. Strategies for improvement include ongoingethics education and training, internal and external supervision, technology integration, and collaboration among legal professionals. Consistent internalization of professional ethics proves to be a key factor in achieving substantive justice and strengthening the legitimacy of the judicial system.